2020
DOI: 10.1002/kjm2.12327
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miR‐409‐3p promotes acute cerebral infarction via suppressing CTRP3

Abstract: Abnormal expression of miR-409-3p has been found in several neurodevelopmental disorders, but whether it is dysregulated in the patients with acute cerebral infarction (ACI) has not been evaluated. The current study mainly focused on the clinical significance and the underlying mechanism of plasma miR-409-3p in the progression of ACI. The level of plasma miR-409-3p was determined in ACI patients (n = 80) and healthy controls (n = 30). Pearson correlation assay was performed to evaluate the association and card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…At present, some microRNAs (miRNAs) have been shown to be involved in ACI pathological processes. [8,9] Additionally, a study by Xiang et al [10] has analyzed the miRNAs with significantly changed expression levels after thrombolytic treatment in patients with ACI, and this study results reveal that miR-106a-5p is significantly downregulated after thrombolysis compared with before thrombolysis. Notably, miR-106a-5p is an atherosclerosis associated miRNA that has been shown to regulate vascularization, endothelial cell and smooth muscle cell activity.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some microRNAs (miRNAs) have been shown to be involved in ACI pathological processes. [8,9] Additionally, a study by Xiang et al [10] has analyzed the miRNAs with significantly changed expression levels after thrombolytic treatment in patients with ACI, and this study results reveal that miR-106a-5p is significantly downregulated after thrombolysis compared with before thrombolysis. Notably, miR-106a-5p is an atherosclerosis associated miRNA that has been shown to regulate vascularization, endothelial cell and smooth muscle cell activity.…”
Section: Introductionmentioning
confidence: 99%
“…8 Additionally, an increased level of miR-409-3p in plasma was correlated with disease severity, making it efficient for the early diagnosis of AIS. 10 Rainer et al also revealed that plasma miR-124-3p and miR-16 could be useful molecular markers for the early prediction of mortality and poststroke modified Rankin Score. 11 The present study investigated two GEO (Gene Expression Omnibus) datasets (GSE110993 and GSE86291) to identify plasma miRNAs that were differentially expressed between AIS and health controls.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study by Eyileten et al found that patients with AIS had significantly higher miR‐19a‐3p and lower let‐7f levels in plasma compared to control patients, with an area under the receiver operating characteristic (ROC) curve of 0.755 for miR‐19a‐3p and 0.874 for let‐7f 8 . Additionally, an increased level of miR‐409‐3p in plasma was correlated with disease severity, making it efficient for the early diagnosis of AIS 10 . Rainer et al also revealed that plasma miR‐124‐3p and miR‐16 could be useful molecular markers for the early prediction of mortality and poststroke modified Rankin Score 11 …”
Section: Introductionmentioning
confidence: 99%
“…miRNA plays an important role in the pathophysiological regulation of cardiovascular diseases and is associated with cerebral ischemia-reperfusion injury and neuronal apoptosis [6,7]. Recently, some brain-specific miRNAs have been identified, and the differential serum levels may be promising indicators for the occurrence and prognosis of ACI, such as miR-409-3p, miR-210, and miR-137 [8,9]. miR-138-5p has been reported to be a protective factor and is involved in a variety of cell damage mechanisms under hypoxia, such as myocardial cell and retinal endothelial cell [10][11][12].…”
Section: Introductionmentioning
confidence: 99%